Implementation of Green HRM at PT Sido Muncul - Arivia, Nadira; Kurniawati, Endah (International Journal of Economics Development Research (IJEDR), 2024)
PT Sido Muncul as one of the major companies in Indonesia has a commitment to environmental sustainability which is reflected in various GHRM practices. The purpose of this study is to explore how the process of implementing the GHRM concept, what are the challenges and obstacles and the impact of GHRM implementation. The method in this research uses qualitative research with data collection techniques, namely literature studies. The data collection used is by collecting, examining, analyzing information or data from various literature sources related to GHRM to understand its implementation and impact. The findings show that PT Sido Muncul has implemented several key GHRM strategies, including training and development, environmental-based performance management, participation in environmental programs, and dialogue with stakeholders. Nonetheless, the company faces challenges such as increasing training initiatives, environmental awareness among employees, as well as the need to continuously develop green practices. Proposed solutions include enhancing training programs, strengthening employee engagement, as well as adjusting policies to overcome existing constraints. This study provides insights into the effectiveness of GHRM in improving environmental performance and contribution to corporate sustainability and provides recommendations to improve the implementation of GHRM in the future.